Review Of Completeness in Filling Out the General Consent Form for Oncological Surgery Polyclinic Patients at Prof. Dr. I.G.N.G. Ngoerah Hospital - I Nyoman Kuta Susila; Made Wahyu Aditya; I G.A.N. Putra Pradnyantara (International Journal of Health Engineering and Technology, 2025)
General consent is a general agreement given by a patient or their family to receive health services, which plays an important role in ensuring the validity of informed consent and legal protection for the hospital. Completeness of this form is crucial so that the information can be clearly understood by the patient and their family, and supports the accountability of health services. This study uses a quantitative method with a descriptive approach. The population used is the general consent documents of outpatients at the Oncology Surgery Clinic of Prof. Dr. I.G.N.G. Ngoerah General Hospital in October - December 2024, totaling 251 documents. The results showed that in the identification aspect, 245 documents (97.6%) were completely filled out. In the authentication aspect, 240 documents (95.6%) were completely filled out, but many still did not include the name of the registration officer. In the recording aspect, only 181 documents (72.1%) were completely filled out, especially the relationship variable with the patient which was often not filled out. Meanwhile, the reporting aspect showed 147 documents (68.6%) were complete, but the recording of the date variable was incomplete. The completeness of the general consent form for outpatients at the Surgical Oncology Clinic of Prof. Dr. I.G.N.G. Ngoerah General Hospital varies. The identification and authentication aspects have been completed well, but recording and reporting aspects require more attention to improve documentation quality and legal protection for the hospital.